OC-071 Screening For Anal Pre-cancer In Hiv Positive And Negative Men Who Have Sex With Men (msm) And Renal Transplant Recipients: Early Experience From A Manchester Based Prospective Study. (9th June 2014) - Schofield, AM; McMahon, R; Sukthankar, A; Desai, M; Hill, J; Patnick, J; Crosbie, EJ; Kitchener, HC
Abstract : Introduction: The UK National Screening Committee has suggested that screening for anal intraepithelial neoplasia (AIN) in populations at high-risk of anal squamous cell carcinoma may be of benefit, but that further information is needed. In these groups the risk of developing anal cancer is increased up-to 100-fold. Methods: ANALOGY is an ongoing prospective cohort study addressing the feasibility and acceptability of anal screening in high-risk groups, based on liquid based cytology (LBC), HPV testing and high-resolution anoscopy (HRA). High-risk patients aged over 25 with no previous history of anal pre-cancer or cancer who are HIV+ men who have sex with men (MSM), HIV- MSM, HIV+ women with a gynaecological neoplasia history or transplant recipients who are 2-years post-procedure were all recruited. All participants had baseline LBC, HPV typing and HRA at recruitment and at 6-months, with a diagnostic biopsy being taken for participants with an abnormal HRA, referral for colorectal opinion was sought in high-grade AIN (HGAIN 3) on biopsy or HSIL on LBC. Data are presented for participants recruited from March 2013. Results: To date, 173 participants have baseline data;78 HIV+ and 25 HIV- MSM, 4 HIV+ women, 42 male and 24 female transplant recipients. Overall 65.8% (114/173) were HPV positive of whom 34.2% (39/114) were HPV 16 positive (30 HIV+ MSM, 7 HIV- MSM, 1 male and 1 female transplant recipients). Abnormal cytology was found in 28.3% (49/173). Abnormal HRA requiring a biopsy was found in 43.3% (75/173) of patients, in HIV+ MSM this proportion was 61.5% (48/78), including 20 high-grade AIN (HGAIN 2 or 3) and one invasive cancer. This constitutes a prevalence of high-grade disease of 26.9% (21/78), 4% (1/25) and 12.5% (3/24) for HIV+, HIV- MSM and renal transplant women respectively. Colorectal referral for HGAIN diagnosed at first visit was required in 7.5% (13/173) of patients, 69.2% (9/13) were HIV+ MSM, 23.1% (3/13) and 7.7% (1/13) were HIV- MSM and a renal transplant woman respectively. Conclusion: Early experience of anal screening in high-risk groups suggests that it is both acceptable and feasible. Colorectal referral for assessment of HGAIN was more frequent in HIV+ MSM than other high-risk groups. These prevalence data are similar to a recently published meta-analysis. Disclosure of Interest: None Declared.